Improving accessibility for outpatients in specialist clinics: reducing long waiting times and waiting lists with a simple analytic approach - Karl Arne Johannessen; Nina Alexandersen (BMC, 2018)
Abstract Background Lack of resources is often cited as a reason for long waiting times and queues in health services. However, recent research indicates these problems are related to factors such as uncoordinated variation of demand and capacity, planning horizons, and lower capacity than the potential of actual resources. This study aimed to demonstrate that long waiting times and wait lists are not necessarily associated with increasing demand or changes in resources. We report how substantial reductions in waiting times/wait lists across a range of specialties was obtained by improvements of basic problems identified through value-stream mapping and unsophisticated analyses. Methods In-depth analyses of current operational processes by value-stream mapping were used to identify bottlenecks and sources of waste. Waiting parameters and measures of demand and resources were assessed monthly from 12 months before the intervention to 6 months after the intervention. The effect of the intervention on reducing waiting time and number of patients waiting were evaluated by a difference-in-differences analysis. Results Mean waiting time across all clinics was reduced from 162 + 69 days (range 74-312 days) at baseline to 52 + 10 days (range 41-74 days) 6 months after the intervention. The time needed to achieve a waiting time of 65 days varied from 4 to 21 months. The number of new patients waiting was reduced from 15,874 (range 369-2980) to 8922 (range 296-1650), and the number of delayed returning patients was reduced from 18,700 (310-3324) to 5993 (40-1337) (p < 0.01 for all). Improvement in waiting measures paralleled a significant increase in planning horizon. Conclusions Significant improvements in accessibility for patients waiting for service may be achieved by applying unsophisticated methods and analyses and without increasing resources. Engagement of clinical management and involvement of front line personnel are important factors for improvement.